Antibodies to CV2/CRMP5 in neuromyelitis optica-like disease: case report and review of the literature - Jarius, Sven; Wildemann, Brigitte (Clinical neurology and neurosurgery, 2012)
Neuromyelitis optica (NMO) is associated with antibodies to aquaporin-4 (termed NMO-IgG or AQP4-Ab) in 60-90% of cases. Little is known about the aetiology of NMO in NMO-IgG/AQP4-Ab negative patients. Here we report on CV2/CRMP5 antibodies in a 69-year-old male patient with NMO-IgG/AQP4-Ab negative NMO. The association of CV2/CRMP5-Ab with prostate cancer suggests a paraneoplastic aetiology of NMO in our patient. Our report strengthens the case of antibodies other than AQP4-Ab being involved in the immunopathogenesis in a subset of patients with NMO. We conclude that CV2/CRMP5-Ab should be included in the differential diagnosis of NMO, in particular if AQP4-Ab are negative and irrespective of whether a tumour is known or not. We recommend that recombinant tests, which are increasingly used because of their higher sensitivity and specificity, should always be accompanied by standard indirect immunofluorescence employing brain tissue sections in order to avoid CV2/CRMP5-Ab or other paraneoplastic antibodies being overlooked. In addition, we provide a comprehensive review of all patients with CV2/CRMP5-Ab and NMO-like disease published in the English literature so far.